METHODOLOGY FOR TRAINING JUDGES IN ORIENTAL MARTIAL ART - Liman, I.V.; Zhalilov, A.V.; Pravdov, D.M.; Zagorodnikova, A.Yu. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a methodology for training judges in oriental martial arts (a group of sports disciplines Shotokan). Methods and structure of the study. At the heart of the experimental methodology for the training of sports referees in Shotokan, verbal and visual methods were used in the form of lectures, tasks of varying degrees of complexity and focus, developing the basic skills and abilities of a sports referee. The pedagogical experiment was carried out during 2021 on the basis of the Federation of Oriental Martial Arts Shotokan in Moscow. The total number of participants in the study was 20 judges of various qualifications. Results and conclusions. The educational course was held for five days. The first day was devoted to the development of theoretical knowledge in the sports discipline Shotokan. Further, for four days at the seminars, the students performed tasks in the form of dictations (dictations of the "protocolist", "judge", "referee") and assessment of various situations in the duel with face-to-face sparring of two athletes on the tatami, presented in the video materials. It is noted that the practice of conducting lectures and seminars, including dictations and assessment of various situations in a duel, makes it possible to cover all aspects of refereeing and contributes to the effective organization and implementation of multilateral training of referees in Shotokan.